Pengelolaan Sumber Daya Pesisir yang Berkelanjutan Bagi Pengembangan Kawasan Pesisir Danau Tempe di Kecamatan Tempe Kabupaten Wajo - Awaluddin, Muhammad Iqbal; Aksa, Kamran; Jufriadi, Jufriadi (Fakultas Teknik Universitas Bosowa, 2023)
Abstract.. Wajo Regency is one of the areas that has enormous potential for coastal resources. One of the coastal areas in Wajo Regency which has a lot of coastal resource potential is Tempe District. The potential of coastal resources in Tempe District is the result of fishery production. Another potential resource that can be developed is tourism development. From this potential, it is necessary to develop coastal areas with sustainable management of coastal resources. This research was conducted to determine the condition of coastal resources and determine sustainable coastal resource management programs in the development of coastal areas in Tempe District. Sustainable coastal resource management is determined based on the results of the SWOT analysis. The results showed that the coastal area in Tempe District which has the highest level of development in conditions of potential coastal resources is located in Tempe Sub-District where the potential for development is tourism and fisheries, then the current level of development is located in Mattirotappareng Village and Salomenraleng Subdistrict with the potential for developing Fisheries and Agriculture . And the low level of development lies in Laelo Subdistrict Village with the potential for coastal resources that can be improved is Agriculture, from these results it is necessary to make several efforts to increase the potential, including preparing land for sustainable tourism development, carrying out the process of preserving and maintaining coastal ecosystems, managing and development of coastal resources in a sustainable manner, in order to grow the community's economy, coastal resources are also not exploited en masse and do not result in adverse impacts in the future. Abstrak. Kabupaten Wajo merupakan salah satu wilayah yang mempunyai potensi sumber daya pesisir yang sangat besar,. Salah satu kawasan pesisir di Kabupaten Wajo yang memiliki potensi sumber daya pesisir yang banyak yaitu Kecamatan Tempe. Potensi sumber daya pesisir Kecamatan Tempe adalah hasil produksi perikanan. Potensi sumber daya lain yang dapat dikembangkan adalah pengembangan pariwisata. Dari potensi tersebut maka diperlukan upaya pengembangan kawasan pesisir dengan pengelolaan sumber daya pesisir yang berkelanjutan. Penelitian ini dilakukan untuk mengetahui kondisi sumber daya pesisir dan menentukan program pengelolaan sumber daya pesisir yang berkelanjutan dalam pengembangan kawasan pesisir di Kecamatan Tempe. Pengelolaan sumber daya pesisir berkelanjutan ditetapkan berdasarkan hasil dari analisis SWOT. Hasil penelitian diperoleh bahwa wilayah pesisir di Kecamatan Tempe yang memiliki tingkat perkembangan kondisi potensi sumber daya pesisir tertinggi terletak pada di Kelurahan Tempe yang potensi pengembangannya adalah pariwisata dan Perikanan, kemudian tingkat perkembangan yang sedang terletak pada Desa Mattirotappareng Dan Kelurahan Salomenraleng dengan potensi pengembangan Perikanan dan Pertanian. Dan tingkat perkembangan yang rendah terletak pada Desa Kelurahan Laelo dengan potensi sumber daya pesisir yang bisa ditingkatkan adalah Pertanian, dari hasil tersebut maka diperlukan beberapa upaya peningkatan potensi, diantaranya adalah menyiapkan lahan untuk pengembangan pariwisata berkelanjutan, melakukan proses pelestarian dan pemeliharaan ekosistem pesisir, pengelolaan dan pengembangan sumber daya pesisir yang benar secara berkelanjutan, agar menumbuhkan perekonomian masyarakat, sumber daya pesisir juga tidak tereksploitasi secara massal dan tidak mengakibatkan dampak buruk dikemudian hari.